2023
DOI: 10.3390/molecules28145403
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Pseudomonas oleovorans Carrying Multidrug Resistance Proteins MdtA and MdtB from Wastewater

Abstract: The pollution of industrial wastewater has become a global issue in terms of economic development and ecological protection. Pseudomonas oleovorans has been studied as a bacterium involved in the treatment of petroleum pollutants. Our study aimed to investigate the physicochemical properties and drug resistance of Pseudomonas oleovorans isolated from industrial wastewater with a high concentration of sulfate compounds. Firstly, Pseudomonas oleovorans was isolated and then identified using matrix-assisted fligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Proteomics found that P. oleovorans has 1781 proteins and P. mendocina has 1745 proteins, but the two are different in mass spectrometry, 16S genes, and several biochemical drug resistance indicators. Considering the close genetic relationship between these two bacteria and the limited selection of genes, it is understandable that there are some similarities, but the two bacteria bring us a very good topic to further study the evolution and function of Pseudomonas oleovorans and Pseudomonas mendocina [37].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics found that P. oleovorans has 1781 proteins and P. mendocina has 1745 proteins, but the two are different in mass spectrometry, 16S genes, and several biochemical drug resistance indicators. Considering the close genetic relationship between these two bacteria and the limited selection of genes, it is understandable that there are some similarities, but the two bacteria bring us a very good topic to further study the evolution and function of Pseudomonas oleovorans and Pseudomonas mendocina [37].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing urbanization and industrialization have brought domestic sewage and industrial wastewater discharge into local water sources and groundwater. Water pollution not only aggravates the deterioration of the ecological environment but also has a certain impact on human health [1]. The increase in industrial wastewater containing organic pollutants further increases toxicity of ecosystems.…”
Section: Introductionmentioning
confidence: 99%